Pengaruh Penggunaan Metode Pendidikan Moral Terhadap Peningkatan Pertimbangan Moral Siswa SMP - Ghony, M. Djunaidi; Ali, Nur (ULUL ALBAB Jurnal Studi Islam, 2001)
The model of learning in teaching moral education widely adopted in Indonesia is the Lecture Question Answer (LQA) method developed from the values induction approach. This method has lent itself to that negative interpretation. The present study attempts at investigating the influences of moral education methods in order to find out a method that is more appropriate to the characteristics and the objectives of moral education in Indonesia. This research is experimental in nature and was performed using a 2x2 factorial design. One independent variable, one moderator variable and one dependent variable were involved in the study. The research subjects were randomly selected from the students of SMP IKIP Malang and they were also randomly assigned to perform research treatments. The subjects’ moral judgment stages were measured using the Kohlberg’s judgment stage structure. A two way anova was then performed to analyze the data. The results show that the method of discussing moral dilemmas is superior to the lecture method. Female students are superior in moral judgment skills than male students.